Fundamentals of Entrepreneurship ENT300 Calzado / Shane Dorian Anak Duntsan... [et.al] - Duntsan, Shane Dorian; Abg Jeffri, Dayang Diyanah Liyana; Fauzi, Ranisah; Harry, Valentino Wesley; Jeffrey, Mohd. Faiz Ikzuwan (2015)
CALZADO is a custom made shoe boutique located at Desa Wira, Jalan Datuk Mohd Musa, 94300 Kota Samarahan, Sarawak. Our business allows the local citizens of Kota Samarahan to satisfy their deepest inner interest in shoe fashion in one convenient location. CALZADO thrives in the shoemaking industry to raise the interest in footwear fashion. It is established to be the best custom made shoe boutique in all of Sarawak region.